Plants traditionally used to make Cantonese slow-cooked soup in China - Yujing Liu; Qi Liu; Ping Li; Deke Xing; Huagang Hu; Lin Li; Xuechen Hu; Chunlin Long (BMC, 2018)
Abstract Background Lǎo huǒ liàng tāng (Cantonese slow-cooked soup, CSCS) is popular in Guangdong, China, and is consumed by Cantonese people worldwide as a delicious appetizer. Because CSCS serves as an important part of family healthcare, medicinal plants and plant-derived products are major components of CSCS. However, a collated record of the diverse plant species and an ethnobotanical investigation of CSCS is lacking. Because of globalization along with a renewed interest in botanical and food therapy, CSCS has attracted a growing attention in soup by industries, scientists, and consumers. This study represents the first attempt to document the plant species used for CSCS in Guangdong, China, and the associated ethnomedical function of plants, including their local names, part(s) used, flavors, nature, preparation before cooking, habitats, and conservation status. Methods In 2014-2017, participatory approaches, open-ended conversations, and semi-structured interviews were conducted with 63 local people and 48 soup restaurant owners (111 interviews) to better understand the biocultural context of CSCS, emphasizing ethnobotanical uses of plants in Guangdong Province, China. Product samples and voucher specimens were collected for taxonomic identification. Mention Index (QI), frequency of use index (FUI), and economic index (EI) were adopted to evaluate the significance of each plant in the food supply. Results A total of 97 plant species belonging to 46 families and 90 genera were recorded as having been used in CSCS in the study area. Recorded menus consisted of one or several plant species, with each one used for different purposes. They were classified into 11 functions, with clearing heat being the most common medicinal function. Of the 97 species, 19 grew only in the wild, 8 species were both wild and cultivated, and 70 species were cultivated. Roots and fruits were the most commonly used plant parts in the preparation of CSCS. According to the national evaluation criteria, six of these species are listed on "China's red list" including two endangered, two critically endangered, one near-threatened, and one vulnerable species. The QI, FUI, and EI of the 97 species in the study varied between 0.09 and 1, 0.23 and 9.95, and 0.45 and 6.58, respectively. Conclusions As an important part of Cantonese culture, CSCS has been popularized as a local cuisine with a healthcare function. CSCS also reflects the plant species richness and cultural diversity of Guangdong Province. Future research on the safety and efficacy of CSCS as well as on ecological and cultural conservation efforts is needed for the sustainable growth of China's botanical and medicinal plant industry.